The Relationship of Mental Workload and Job Stress in Assembly Operators at PT. X Year 2024 - Diina Maulina; Krismadies Krismadies (Syntax Idea)
The manufacturing industry often involves repetitive and monotonous work, especially in the assembly section. This job requires not only physical skills but also a significant mental workload. This research aims to analyze the relationship between mental workload and work stress in assembly operators at PT. X year 2024. This research uses quantitative methods. The data collection technique used in this research was the NASA-TLX questionnaire. The data analysis technique used is descriptive analysis. The research results show that mental workload has a positive relationship with work stress in assembly operators at PT. X in 2024. Based on the results of the questionnaire, data was obtained that 12 out of 30 workers experienced very high mental workload. Meanwhile, in terms of work stress, from the aspect of role ambiguity and role conflict, all respondents felt mild stress, in the qualitative overload aspect, 5 out of 30 workers experienced severe stress and the rest were moderate stress, while in the career development aspect, 1 person felt severe stress and the remaining 29 experienced moderate stress, finally the aspect responsibility towards others 4 people experienced severe stress and 26 others experienced mild stress